The Effect Of Digital Competence and Work Motivation on Employee Performance with Self-Efficacy as an Intervening Variable at The Langkat Regency Communication and Information Office - Yudha Wardana Ginting; Sri Rahayu; Mesra B (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of Digital Competence and Work Motivation on Employee Performance, with Self-Efficacy as an intervening variable at the Lalat Regency Communication and Information Office. This study uses a quantitative approach with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method to test the direct and indirect relationship between variables. Primary data was collected through the distribution of questionnaires to employees, then analyzed using internal model testing and mediation tests. The results of the hypothesis test showed that Digital Competency did not have a significant effect directly on Employee Performance (β = −0.044; T = 0.212; P = 0.834), which indicates that improving digital capabilities alone is not enough to improve employee performance. On the other hand, Work Motivation has a positive and significant effect on Employee Performance (β = 1.055; T = 8.008; P = 0.000), which confirms the dominant role of work motivation in encouraging employee performance improvement. Furthermore, Digital Competency had a significant effect on Self-Efficacy (β = 0.719; T = 2,896; P = 0.007), while Work Motivation had no significant effect on Self-Efficacy (β = 0.174; T = 0.684; P = 0.500). However, Self-Efficacy did not have a significant effect on Employee Performance (β = −0.062; T = 0.460; P = 0.649). The results of the indirect influence analysis showed that Self-Efficacy was not able to mediate the relationship between Digital Competence and Employee Performance (β = −0.045; T = 0.345; P = 0.733), as well as the relationship between Work Motivation and Employee Performance (β = −0.011; T = 0.254; P = 0.801). Based on these findings, it can be concluded that Digital Competency is the only variable that has a direct and significant effect on Employee Performance.